Citizens Views on Policy Instruments for Sustainable Food Consumption From Spatial Perspective - Matschoss, Kaisa (Frontiers in Sustainability, 2022)
Abstract To mitigate climate change, large GHG emission reductions need to be made in several sectors of the consumer society. This calls for policy instruments that guide citizens in adapting their behavior. In Finland, a mid-range climate strategy is set for each governmental period to reach GHG emission reductions. For the renewal of the strategy, the Ministry of the Environment organized a citizen survey in 2021 to gain better understanding on how citizens perceive the impact of selected policy instruments and what kinds of actions citizens imagine taking to reduce their consumption. More than 18.000 citizens replied to the survey. This research analyses the perceptions of citizens in how different policy instruments related to food target respondents in different residential areas. The responses are examined for urban, peri-urban and rural areas to find out whether there are differences in how respondents in different spatial context perceive the impact of the policy instruments. The analysis reveals that there are small but statistically significant differences in results depending on the area of residence. People living in rural areas consider themselves to be more impacted by most policies than the urban residents. Responses to open-ended questions are analyzed to find out how people imagine how they could increase the share of plant-based food in their diets and reduce food loss and whether there is a difference in responses between urban and rural responses. Suggestions for future policy design for food consumption are made based on the findings.